Careful control: The infrastructure of water in carceral space. Issue 2 (8th June 2018) - Turner, Jennifer; Moran, Dominique
Abstract : This paper advances carceral geographies by situating water in relation to the nexus of care and control in the carceral setting. Critical for both hygiene and health, but also requiring control and management, consideration of water offers an analytical lens to uncover everyday, intimate and embodied institutional spaces of care and control mediated by water both in its elemental form, and via water infrastructures. Drawing on extensive qualitative data generated with serving prisoners in the UK, the paper considers carceral relationships with water as variously and simultaneously unruly, restrictive, health‐enabling and therapeutic.